Predictive value of pre‐operative inflammation‐based prognostic scores (neutrophil‐to‐lymphocyte ratio, platelet‐to‐lymphocyte ratio, and monocyte‐to‐eosinophil ratio) in testicular sperm extraction: a pilot study. (9th October 2017) - Yucel, C.; Keskin, M. Z.; Cakmak, O.; Ergani, B.; Kose, C.; Celik, O.; Islamoglu, E.; Ucar, M.; Koc, G.; Kozacioglu, Z.
Summary: To investigate the ability of some hematologic prognostic scores demonstrating inflammation in predicting sperm presence in testicular sperm extraction (TESE). We retrospectively investigated the medical data of 430 patients with the diagnosis of non‐obstruc tive azoospermia (NOA) who had undergone TESE operation consecutively in our institution between the dates of January 2009 and February 2017. In all, 352 patients with the diagnosis of NOA, with bilaterally palpable vas deferens, who had undergone TESE for the first time, were included in the study. Patients with genetic anomalies, genital infection, history of surgery or vasectomy, chronic diseases, history of inflammatory, metabolic, rheumatologic, or malignant diseases, morbid obesity, with the diagnosis of clinical varicocele, or patients who had undergone TESE for the second time were excluded from the study. According to the results of TESE, the patients were divided into two groups as those with sperm retrieval and those without sperm retrieval. These groups were compared in terms of age, infertility duration, body mass index, hormone profile, hematologic parameters, neutrophil‐to‐lymphocyte ratio (NRL), monocyte‐to‐eosinophil ratio (MER), and platelet‐to‐lymphocyte ratio (PLR). The NLR and PLR levels were found to be significantly higher in patients without sperm retrieval at TESE compared to those with sperm retrieval. The logistic regression analysis showed NLR as an independent factor that showed the presence of spermatozoa at TESE (odds ratio: 4.786, %95 confidence interval: 2.667–8.589, p  < 0.001). The area under the ROC curve (AUC) for the PLR was determined to be 0.574. As the calculated AUC value of the PLR was below 0.6, there was insufficient evidence determined at TESE to say that it was a reliable marker to indicate the presence of spermatozoa. The area of the MER value under the ROC curve was not statistically significant. It has been demonstrated that systemic inflammation negatively affects the probability of extracting spermatozoa in TESE and NLR is an independent factor indicating the presence of spermatozoa in TESE.